2012
DOI: 10.1099/jmm.0.038695-0
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic valve endocarditis caused by Bordetella holmesii, an Acinetobacter lookalike

Abstract: We report a case of fulminant endocarditis on a prosthetic homograft aortic valve caused by Bordetella holmesii, which was successfully managed by surgical valve replacement and antibiotic treatment. B. holmesii, a strictly aerobic, small, Gram-negative coccobacillus, has been implicated as an infrequent cause of a pertussis-like syndrome and other respiratory illnesses. However, B. holmesii is also a rare cause of septicaemia and infective endocarditis, mostly in immunocompromised patients. To our knowledge, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 14 publications
1
11
0
1
Order By: Relevance
“…Bho1 and FR4020 present a bhoE sequence identical to that in GenBank (DQ402419). OmpA, encoding a porin-like protein, is sometimes preferred for identification purposes, because it displays a higher degree of mutational variation than 16S rRNA [12]. The sequences of ompA in Bho1 and FR4020 were 100% identical to that in GenBank for other B. holmesii isolates (Accession no.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bho1 and FR4020 present a bhoE sequence identical to that in GenBank (DQ402419). OmpA, encoding a porin-like protein, is sometimes preferred for identification purposes, because it displays a higher degree of mutational variation than 16S rRNA [12]. The sequences of ompA in Bho1 and FR4020 were 100% identical to that in GenBank for other B. holmesii isolates (Accession no.…”
Section: Discussionmentioning
confidence: 99%
“…This poses a potential problem, because the diagnosis of B. pertussis infection is based on the PCR detection of IS481 sequences. The development of specific PCR diagnosis for B. holmesii infection, targeting the recA gene [7][8][9], or the transposase IS1001bho [10], the amplification of specific target as bhoE [11] or the sequencing of 16sRNA or OmpA [12] has made it possible for a number of retrospective studies to demonstrate an increase in the number of reported cases of respiratory infections due to B. holmesii over the last few years [10,11,[13][14][15][16][17][18][19][20][21]. We wondered whether this increase in detection reflected a real increase in the number of infections or was simply a consequence of the increasing use of RT-PCR targeting IS481 for the diagnosis of B. pertussis since 2005.…”
Section: Introductionmentioning
confidence: 99%
“…A recent report described four adolescents lacking normal splenic function who presented with mild febrile illness and had B. holmesii bacteremia (4); there has also been a description of septic arthritis caused by B. holmesii in an adolescent with chronic hemolytic anemia who was asplenic and had no concom-itant bacteremia (11). A number of other very recent reports document pericardial and endocardial infection with B. holmesii in immunocompromised adults (5,12,13).…”
Section: Discussion B Holmesii Was First Isolated In 1983 and Was Dmentioning
confidence: 99%
“…Cellular fatty acid profiles and 16S rRNA gene sequencing are useful for making a definitive identification (3). Matrix-assisted laser desorption ionization-time of flight mass spectrometry has also been shown to have a role in the identification of many bacteria; this technology has been used to successfully identify B. holmesii (5,6).…”
Section: Discussion B Holmesii Was First Isolated In 1983 and Was Dmentioning
confidence: 99%
“…DNA was extracted from fresh colonies grown on blood agar (homemade Columbia agar supplemented with 5% horse blood) using the QIAamp DNA minikit (Qiagen, Hilden, Germany) in accordance with the manufacturer's instructions. The bacterial 16S rRNA gene was amplified using the following primers: 5=-AGA GTT TGA TCC TGG CTC AG-3= (forward; Escherichia coli positions 8 to 27) and 5=-TAC CTT GTT ACG ACT TCG TCC CA-3= (reverse; E. coli positions 1504 to 1485) (1,2). Amplification products of approximately 1,350 nucleotides (nt) were checked by agarose gel electrophoresis (2%) and visualized through ethidium bromide staining.…”
mentioning
confidence: 99%